Routledge handbook of Southeast Asian economics - Coxhead, Ian A.; Williamson, Jeffrey G., 1935- (New York : Routledge, 2015)
'Offers a new insight into the rapidly-developing picture of economics in Southeast Asia. The countries of the region display a great variety of development experiences. Its character is increasingly dominated by the region's ever-closer integration into the wider East Asian network of primary and secondary production and trade. A second striking feature of the Southeast Asia's development is the pace and extent of transformation of production and sources of household income. Since the 1980s the region as a whole has achieved and sustained a remarkable rate of growth, in the course of which tens of millions of its citizens have successfully escaped severe poverty. This handbook offers a timely and comprehensive overview of Southeast Asian economic development'--
Southeast Asia's long transition / Ian Coxhead -- The commodity export, growth and distribution connection in Southeast Asia, 1500-1940 / Jeffrey Williamson -- A century of growth, crisis, war and recovery, 1870-1970 / Anne Booth -- Lucky countries? : internal and external sources of Southeast Asian growth since 1970 / Tracy Phung, Ian Coxhead, and Chang Lian -- The dynamics of agricultural development and food security in Southeast Asia : historical continuity and rapid change / C. Peter Timmer -- Natural resources, the environment and economic development in Southeast Asia / Gerald Shively and Tim Smith -- Global production sharing and trade patterns in Southeast Asia / Prema-Chandra Athukorala and Archanun Kohpaiboon -- Foreign direct investment in Southeast Asia / Fredrik Sjolm -- Regional trade agreements and enterprises in Southeast Asia / Ganesh Wignaraja -- The population of Southeast Asia / Gavin Jones -- The determinants and long-term projections of saving rates in Southeast Asia / Charles Horioka and Akiko Terada-Hagiwara -- Education in Southeast Asia : investment, achievements and returns / Diep Phan and Ian Coxhead -- Internal and international migration in Southeast Asia / Guntur Sugiyarto -- The contribution of economic growth to poverty reduction / Peter Warr -- The political economy of policy reform : insights from Southeast Asia / Hal Hill -- Dual-burdens in health and aging : emerging population challenges in Southeast Asia / Jenna Nobles -- Southeast Asian commercial policy : outward-looking regional integration / Hal Hill and Jayant Menon -- Macroeconomic policy and the global financial crisis / Bhanupong Nidhiprabha -- Twenty-first century challenges / Ian Coxhead, Thee Kian Wee and Arief Anshory Yusuf.
Includes bibliographical references and index.
Keywords: Economic development -- Southeast Asia; Southeast Asia -- Economic conditions